Cholinesterase-based biosensor using Lates calcarifer (Asian Seabass) brain for detection of heavy metals - Hayat N.M.; Shamaan N.A.; Shukor M.Y.; Sabullah M.K.; Syed M.A.; Khalid A.; Dahalan F.A.; Khalil K.A.; Ahmad S.A. (SPB Pharma Society, 2024)
Indexed by Scopus